The chemical oxidation of trichloroethylene (TCE) and tetrachloroethylene (PCE) in contaminated aqueous and soil systems using modified Fenton's chemistry - Go, Jason V. (2003)
Chlorinated solvents indiscriminately disposed to the subsurface impacts not only the soil but may potentially contaminate the groundwater thus impacting the human health as well. Residual contaminants are left in the pores of the soil matrix as the solvent migrate in the subsurface, which in turn may serve as long term source of groundwater contamination. Treatment and removal of these contaminants may be facilitated by chemical oxidation using Fenton's chemistry. Hydroxyl radiclas formed by the action of hydrogen peroxide and the ferrous ion catalyst chemically degrade these organic compounds to relatively benign by products such as carbon dioxide, water and metallic salts.
In the study, the viability and efficacy of using Fenton-like chemistry in the chemical oxidation of chlorinated solvents, specifically trichloroethylene (TCE) and tetrachloroethylene (PCE) in contaminated aqueous and soil systems was evaluated. The study was divided in two experimental phases which included aqueous studies and soil vial experiments.
Bench-scale treatability studies done on the TCE and PCE contaminated aqueous and soil samples maintained at near neutral pH conditions showed significant contaminant removal. Aqueous samples treated with 0.521 M hydrogen peroxide and 1:1 (M/M) chelated concentration ratio resulted to 95.83±5.28% COD removal. Soil vial experiments conducted on contaminated soil samples using GC headspace analysis resulted to 93.62± 0.34% TCE and 94.40±0.35% PCE removal upon treatment. The reagent mass loading rate to the soil samples was 20000 mg hydrogen peoxide, 0.0271 mg iron and 0.00789 mg citric acid per kg of soil. The experimental results, hence, show conclusively that chemical treatment based on Fenton-like chemistry is technically viable in removing organics in both aqueous and soil systems maintained at near neutral p
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Trichloroethyle; Tetrachloroethyle